Relationship of lightning with different weather parameters during transition period of dry to wet season over Indian region. (1st September 2021) - Tinmaker, M.I.R.; Jena, Chinmay K.; Ghude, Sachin D.; Dwivedi, Arun Kumar; Islam, Sahidul; Kulkarni, Santosh H.; Khare, Manoj K.; Chate, D.M.
Abstract: This paper presents a relationship of lightning activity with maximum air temperature, Bowen ratio, rainfall, cloud ice contents and Aerosol Optical Depth (AOD) over India during transition period from dry to wet seasons. Lightning flash count data and weather parameters are retrieved from the Tropical Rainfall Measuring Mission (Lightning Imaging Sensor - LIS) and the Moderate Resolution Imaging Spectroradiometer (MODIS) satellites for the period of 17 years (1998–2014). The Pearson correlation between lightning flash count and Bowen ratio is found to be coefficient of R = 0.95 for both dry and wet seasons. For dry season, the Pearson correlation of lightning flash count with surface maximum air temperature is found to be coefficient of R = 0.97 whereas, that for wet season negative coefficient of R = −0.89. The comparative analysis of Pearson correlations of lightning flash counts with AOD, rainfall and cloud ice content are found to be coefficients higher by 20%, 28% and 34% for dry season than those of during wet season, respectively. The results of lightning activity and weather parameters in comparative analyses over the Indian region may be useful for better understanding the differential convection characteristics during transition period of dry to wet season. The results are also important for estimations of impact associated with lightning strikes to ground during dry and wet seasons. Highlights: Lightning activity and its relationship with weather parameters during transition from dry to wet season over Indian region. The flash count is found to be high during dry season as compared to wet season. Bowen ratio plays important role in the formation of thunderstorm and lightning.